Micro-RNAS Regulate Metabolic Syndrome-induced Senescence in Porcine Adipose Tissue-derived Mesenchymal Stem Cells through the P16/MAPK Pathway. Issue 10 (October 2018) - Meng, Y.; Eirin, A.; Zhu, X.-Y.; Tang, H.; Hickson, L.J.; Lerman, A.; van Wijnen, A.J.; Lerman, L.O.
Mesenchymal stem cells (MSCs) constitute an important repair system, but may be impaired by exposure to cardiovascular risk factors. Consequently, adipose tissue-derived MSCs from pigs with the metabolic syndrome (MetS) show decreased vitality. A growing number of microRNAs (miRNAs) are recognized as key modulators of senescence, but their role in regulating senescence in MSC in MetS is unclear. We tested the hypothesis that MetS upregulates in MSC expression of miRNAs that can serve as post-transcriptional regulators of senescence-associated (SA) genes. MSCs were collected from swine abdominal adipose tissue after 16 weeks of Lean or Obese diet ( n = 6 each). Next-generation miRNA sequencing (miRNA-seq) was performed to identify miRNAs up-or down-regulated in MetS-MSCs compared with Lean-MSCs. Functional pathways of SA genes targeted by miRNAs were analyzed using gene ontology. MSC senescence was evaluated by p16 and p21 immunoreactivity, H2AX protein expression, and SA-β-Galactosidase activity. In addition, gene expression of p16, p21, MAPK3 (ERK1) and MAPK14, and MSC migration were studied after inhibition of SA-miR-27b. Senescence biomarkers were significantly elevated in MetS-MSCs. We found seven upregulated miRNAs, including miR-27b, and three downregulated miRNAs in MetS-MSCs, which regulate 35 SA genes, particularly MAPK signaling. Inhibition of miR-27b in cultured MSCs downregulated p16 and MARP3 genes, and increased MSC migration. MetS modulates MSC expression of SA-miRNAs that may regulate their senescence, and the p16 pathway seems to play an important role in MetS-induced MSC senescence.